Double aortic arches, esophageal atresia and tracheal compression - Majid Yameen; Warade Monali; Aziz Zarina; Karthik G (Wolters Kluwer Medknow Publications, 2009)
We report a case of double aortic arch in a 12-month-old male infant well delineated on 64 slice computed tomography scan. It formed a complete vascular ring around the trachea compressing it. The symptoms resolved after surgical division of the ring.